A Cluster Analysis with Complete Linkage and Ward's Method for Health Service Data in Makassar City - Isma Muthahharah; Agusalim Juhari (Universitas Bumigora, 2021)
Health care facilities are a place used to organize health efforts. Health service data in Makassar City has not shown which sub-districts have excellent service criteria, good enough, and not good. Therefore, it is necessary to group sub-districts with cluster analysis using hierarchy method. The hierarchy method used in this study is only 2, namely complete linkage and ward's method. Complete linkage method is the opposite of the approach to the minimum distance principle that is the furthest distance between objects while Ward's Method is a method that aims to minimize variance between objects in one cluster. There are four health services used, namely Hospitals, Health Centers, Home Care and Telemedicine with 15 sub-districts. This study also used a validity test namely Index Davies Bouldin (IDB) to determine the criteria of health services. The results of the analysis on complete linkage formed 3 clusters, namely cluster 1 with good health services, cluster 2 with excellent health services, and cluster 3 with poor health services. In addition, ward's Method also formed 3 clusters, namely cluster 1 with good health services, clusters 2 with poor service, and cluster 3 with excellent health services.